N,N,N′,N′-Tetrakis(pyridin-4-yl)methanediamine monohydrate - Shin, Jong Won (International Union of Crystallography, 2012)
In the title compound, C(21)H(18)N(6)·H(2)O, two 4,4′-dipyridylamine groups are linked by a methylene C atom, which sits on a twofold axis. The lattice water molecule is located slightly off a twofold axis, and is therefore disordered over two positions. In the crystal, the organic molecules and the water molecule are linked by O—H⋯N hydrogen bonds. The organic molecules exhibit extensive offset face-to-face π–π interactions to symmetry equivalents [centroid–centroid distances = 3.725 (3) and 4.059 (3) Å].